Efficacy of Different Oocytes Harvesting Methods on Retrieval and Quality of Oocyte from Ovaries of Local Cows (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The aim of this study was to investigate the effect of different oocytes harvesting  methods on retrieval and quality of oocyte from ovarian of local cows.  The ovaries (n = 600) were collected from 300 non-pregnant cows their ages ranged between (3-10 years old), slaughtered at the abattoir of Babylon province during the period between September 2017 to March 2018. The oocytes were collected by slicing method, puncture method and aspiration of follicle method and classified according to layers of cumulus cells and the homogenous of cytoplasm into three groups , first group : good quality oocytes with more than 3 layers of cumulus cells and homogeneous of cytoplasm, second group : fair quality oocytes with less than 3 layers of cumulus cells and homogeneous of cytoplasm , third group : poor quality oocytes , denuded oocyte from cumulus cells with heterogeneous cytoplasm . The results showed that the total number of oocytes recovered and the number of oocytes recovered  per ovary was significantly higher (P